ECONOMICS OF EGG PRICE, CONSUMPTION, AND INCOME OF LAYING HEN FARMERS DURING OF COVID-19 PANDEMIC IN CENTRAL JAVA, INDONESIA - Agus Setiadi; Siswanto Imam Santoso; Suryani Nurfadillah; Kadhung Prayoga; Joko Mariyono (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Covid-19 pandemic has changed the economic condition that hit agricultural sectors. The study aimed to investigate the condition of egg price, egg consumption, and income of laying hen farmers during the Covid-19 pandemic on in Central Java. One hundred and ten laying hen farmers in Kendal, Central Java, Indonesia, were observed and interviewed. Kendal regency is one of the laying-hen producers in Indonesia. A survey was used to collect data before and during the pandemic. Secondary data were taken from the Ministry of Agriculture. A t-test analysis was used to investigate the effect pandemic on consumption and income. Regression analysis was used to determine the effect of supply, demand, and egg price on laying hen farmer income during the pandemic. Consumption of eggs dropped by 20% due to the pandemic. The egg price declined due to limited transportation and distribution caused by lockdown policy. The pandemic has suppressed the income of the laying hen farmers, thought supply-demand mechanism, as during the pandemic the income sharply dropped. The egg price started increasing in June 2020 after the government relaxed the lockdown. This escalated egg price, laying hen farmers’ income, and egg consumption. The increasing supply, demand, and egg price increased farmers’ income. The government needs to provide an economic stimulus to make the industry survives, and to ensure the community consumes enough eggs. The stimulus could be a form of subsidy to producers and consumers.